Cretan Pictographs and Prae-Phoenician Script : With an Account of a Sepulchral Deposit at Hagios Onuphrios near Phaestos in its Relation to Primitive Cretan and Aegean Culture - Evans, Arthur (Cambridge library collection. Archaeology, 1895)
Sir Arthur John Evans (1851–1941) famously excavated the ruins of Knossos on Crete and uncovered the remains of its Bronze Age Minoan civilisation (as described in his multi-volume work The Palace of Minos at Knossos, also reissued in this series). But he had already visited the island prior to this: in 1894, during his first trip, he found examples of an ancient pictographic writing system that pre-dated the Phoenician alphabet later adapted by the Greeks. First published in 1895, this work, illustrated with examples throughout, documents and describes these discoveries, and demonstrates that the earliest finds date from a period before even the most ancient known Semitic scripts. Evans also records evidence of later scripts which were subsequently categorised as Linear A and Linear B (only the latter has been deciphered since his death). The final section of the book describes in detail the pottery and other finds from the Hagios Onuphrios deposit.